Analisis Ruang Lingkup Studi Al Qur’an Cabang Kajian Keterkaitan dengan Ilmu Tafsir - Totussangadah, Robit; Ahmad Kafi Hamdi (Edupedia Publisher, 2024)
This paper aims to find out the scope, branches of study, and the relationship between Qur'anic Studies and the science of Tafsir. This research is a type of library research with content analysis. The results of this study show: 1) The scope of Qur'anic studies includes aspects of linguistics, history, and Islamic law; 2) Branches of study include Qur'anic sciences such as Science of al-Qira'at, Science of al-Tafsir, and Science of al-Hadith; 3) The relationship between Ulum al-Qur'an and the science of Tafsir includes contextual understanding, hermeneutics, and tafsir methodology.